Enhanced high‐temperature resistance and magnetic property of SiFeC nanocomposites containing a small amount of boron. Issue 2 (25th September 2021) - Yang, Le; Feng, Yao; Riedel, Ralf; Yu, Zhaoju
Abstract: In this paper, the boron‐modified polyferrocenylcarbosilanes (namely HBPFCS‐Bs) with hyperbranched structure, as single‐source‐precursors, were successfully prepared by using 9‐borabicyclo [3, 3, 1] nonane (9‐BBN) and polyferrocenylcarbosilanes (HBPFCSs) as starting materials. The obtained HBPFCS‐Bs were characterized using Fourier transform infrared spectroscopy (FT‐IR), nuclear magnetic resonance spectroscopy (NMR) and gel permeation chromatography (GPC), providing that the boron element can be introduced into the HBPFCS chains by the hydroboration (B‐H/C = C) reaction. Then, the structural evolution of HBPFCS‐Bs and the boron‐containing SiFeC ceramics at different temperatures (1100–1500°C) was further investigated by thermogravimetric analysis, X‐ray diffraction, energy dispersive spectroscopy, scanning electron microscope, and transmission electron microscopy. The results show that the incorporation of a small amount of boron (1 wt%) into precursors significantly improves the properties of the final ceramics, including the significant increase of the ceramic yield, enhanced high‐temperature resistance, as well as the higher ceramic densification. Finally, the saturation magnetization of the HBPFCS‐Bs‐derived ceramics was also enhanced by the introduction of boron.